Liberal Egalitarianism and the Harm Principle - Michele Lombardi; Kaname Miyagishima; Roberto Veneziani (University of Massachusetts, Department of Economics, 2013)
This paper analyses the implications of classical liberal and libertarian approaches for distributive justice in the context of social welfare orderings. An axiom capturing a liberal non-interfering view of society, named the Weak Harm Principle, is studied, whose roots can be traced back to John Stuart Mill s essay On Liberty. It is shown that liberal views of individual autonomy and freedom can provide consistent foundations for social welfare judgements, in both the finite and the infinite context. In particular, a liberal non-interfering approach can help to adjudicate some fundamental distributive issues relative to intergenerational justice. However, a surprisingly strong and general relation is established between liberal views of individual autonomy and non-interference, and egalitarian principles in the Rawlsian tradition. JEL Categories:
Keywords: D63; D70; Q01; 330; Liberal principles; maximin; intergenerational equity; infinite utility streams